PROBLEMS OF ORGANIZATIONAL AND LEGAL DEVELOPMENT OF AGRICULTURAL COOPERATION OF THE REPUBLIC OF KAZAKHSTAN - Kuandykov Қалдарбек Жүнісбайұлы; Zhusupbekova Мадина Қойшыбайқызы; Abdrakhmanov Рахат Зауытбекұлы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
The article deals with topical issues of organizational and legal development of agricultural cooperation, identifies resolvable and complex problems that arise when organizing agricultural cooperation in the country. At the same time, international practice and the opinions of various scientists on the support of agricultural cooperation are considered. The article analyzes the achievements in the development of agricultural cooperation of civilized countries, the present situation of domestic agricultural producers. According to the Law of the Republic of Kazakhstan “On Agricultural Cooperatives”, an analysis was made of the legal status of agricultural cooperatives as commercial legal entities. The article points out the problems of constantly attracting private and state investments for the development of agricultural infrastructure at the state level. In addition, the problems of the need for comprehensive state support of agricultural entities, organized in the form of a cooperative. The article indicates that the state support of agricultural cooperatives provides food security, solves the problems of employment and economic development of the country. The creation by rural residents of a larger number of agricultural cooperatives would have affected such problems as: providing the population with work, increasing the well-being of the people and providing the country with high-quality food. At the same time, the article identifies the problems that need to be solved for the development of agricultural cooperation.